The Influence of the Work Creation Law Draft on Abnormal Return and Trading Volume Activity in LQ45 Share - Ansorimal; Harry Patuan Panjaitan; Teddy Chandra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the effect of the event on the work copyright bill on abnormal returns and trading volume activity on LQ45 shares on the Indonesian stock exchange. It is hoped that the findings of this study can contribute to the development of studies on financial management. The research population is LQ45 companies listed on the IDX in 2020, with secondary data collection from sites (Yahoo Finance, n.d.) and (Indonesian Stock Exchange, n.d.). Quantitative research data analysis techniques used in the form of descriptive analysis techniques, hypothesis analysis. Testing the data from this research is in the form of a t-hypothesis test, and by using the Ms. excel. The results of this study found that there was no difference in abnormal returns before and after the events studied and also there is no difference in trading volume activity before and after the events studied.